Analisis Pengaruh Pelaksanaan Praktek Kerja Lapangan Industri terhadap Peningkatan Keterampilan Praktis Siswa Jurusan Teknik Elektro - Laila, Hadaya Rahma; Sari, Mutia Indah; Nurolivia, Serin; Fua’din, Ahmad (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This study aims to analyse the effect of Industrial Field Work Practice on improving the practical skills of students majoring in electrical engineering at the State Vocational High School 1 Katapang. The research methods used include surveys and case studies, with a population of students from the electrical engineering department at the school. Data collection was conducted through a survey by distributing questionnaires to students related to field work practice and their readiness to enter the world of work. The results showed that Industrial Field Work Practices had a significant impact in the development of students' practical skills, with most students reporting a marked improvement in their skills. The implication of this study is the importance of improving the quality of Industrial Field Practice programmes to provide optimal benefits for students and industry, as well as preparing students with solid skills to enter the world of work.